Probabilistic Seismic Hazard Analysis Using the New Correlation Relationships for Magnitude Scales - Behrooz Alizadeh; Saeid Pourzeynali (Civil Engineering Journal, 2018)
Amol is one of the oldest cities located in north of Iran, Mazandaran province, and its history dates back to the pre-Islamic period. Amol is a city with an area about 3000 square kilometers, a population exceeding 370,000, and includes the old and famous neighborhoods that have a religious, commercial, and service with a long history background. Considering the importance of buildings constructed in this city and the need for their preservation and restoration on one hand, and the occurrence of many severe earthquakes in the past centuries, as well as the recent earthquakes of the last century, on the other hand, encourage us to study the seismicity of this city. Therefore, in this paper, by considering the historical and instrumental earthquakes recorded within a radius of 150 km around this city and the seismic mechanism of the faults located in this region, probabilistic seismic hazard analysis of the area is studied. Then, using the probabilistic relations of the seismic hazard analysis of the Kijko 2000 computer program, the seismicity parameters and the return periods of the earthquake magnitudes are obtained for the area, and at the end, the horizontal peak ground acceleration is zoned for this city.